Comparative Effectiveness of High-Intensity Interval Training and Moderate-Intensity Continuous Training for Cardiometabolic Risk Factors and Cardiorespiratory Fitness in Childhood Obesity: A Meta-Analysis of Randomized Controlled Trials - Liu, Jingxin; Zhu, Lin; Su, Yu (Frontiers in Physiology, 2020)
Purpose: The main objective of this meta-analysis was to compare the effectiveness of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on cardiometabolic health in childhood obesity and determine whether HIIT is a superior form of training in managing obese children’s metabolic health. Methods: Relevant studies published in PubMed, Web of Science, Embase, the Cochrane Library, EBSCO, and CNKI were searched with restriction from inception to 1 October 2019. Only randomized controlled trials (RCTs) depicting the effect of HIIT on childhood obesity were included. Results: Nine RCTs involving 309 participants were included in the meta-analysis. Among the 309 participants, 158 subjects were randomized for HIIT, while the others were randomized for MICT. Significant differences were observed in the body weight [mean difference (MD) = −5.45 kg, p = 0.001)], body mass index (BMI; MD = −1.661 kg/m2, p = 0.0001), systolic blood pressure (SBP; MD = −3.994 mmHg, p = 0.003), and diastolic blood pressure (DBP; MD = −3.087 mmHg, p = 0.0001) in the HIIT group relative to the baseline values. Similar effects were found in the MICT group, as depicted by the significantly decreased values on body weight (MD = −4.604 kg, p = 0.0001), BMI (MD = −2.366 kg/m2, p = 0.0001), SBP (MD = −3.089 mmHg, p = 0.019), and DBP (MD = −3.087 mmHg, p = 0.0001). However, no significant differences were observed in the changes in body weight, BMI, SBP, or DBP between the HIIT and MICT groups. Furthermore, our studies showed that both HIIT and MICT can significantly improve VO2peak (HIIT, MD = 4.17 ml/kg/min, p = 0.0001; MICT, MD = 1.704 ml/kg/min, p = 0.019). HIIT also showed more positive effects on VO2peak (SMD = 0.468, p = 0.006) than MICT. Conclusion: HIIT positively affects the cardiometabolic risk factors in childhood obesity, and similar positive effects on body composition and blood pressure were established. Moreover, HIIT can improve cardiorespiratory fitness more significantly than MICT. These findings indicate that HIIT may be an alternative and effective training method for managing childhood obesity.